2020
DOI: 10.3390/plants9121721
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Anthocyanins and Other Phytochemicals in American Elderberry Cultivars during Fruit Ripening and its Impact on Color Expression

Abstract: American elderberry (Sambucus canadensis) is a plant native to North America with anthocyanin-rich fruits. Our objective was to investigate the effects of cultivar and ripeness on the phytochemical characteristics of its fruits and the corresponding color performance. Cultivars ‘Adams’, ‘Johns’, ‘Nova’, ‘Wyldewood’, and ‘York’ were examined for their °Brix, pH, anthocyanin (pH-differential method), and phenolic content (Folin-Ciocalteau method). Extract composition were analyzed by uHPLC-PDA-MS/MS. Color and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 34 publications
5
25
1
Order By: Relevance
“…The pH of the bilberry pulp was 3.12, which was lower than the pH of strawberry (3.57) and elderberry (3.84). These results are in agreement with findings of other researchers who investigated properties of elderberry (Vujanović et al, 2020;Zhou et al, 2020) and bilberry (Bernal et al, 2014;Colak et al, 2016;Celik et al, 2018). Titratable acidity of all three investigated fruits was within the same range (1.22-1.28% citric acid) and is in good agreement with literature data (Vulić et al, 2008;Özgen et al, 2010;Colak et al, 2016;Celik et al, 2018).…”
Section: Chemical Compositionsupporting
confidence: 93%
See 1 more Smart Citation
“…The pH of the bilberry pulp was 3.12, which was lower than the pH of strawberry (3.57) and elderberry (3.84). These results are in agreement with findings of other researchers who investigated properties of elderberry (Vujanović et al, 2020;Zhou et al, 2020) and bilberry (Bernal et al, 2014;Colak et al, 2016;Celik et al, 2018). Titratable acidity of all three investigated fruits was within the same range (1.22-1.28% citric acid) and is in good agreement with literature data (Vulić et al, 2008;Özgen et al, 2010;Colak et al, 2016;Celik et al, 2018).…”
Section: Chemical Compositionsupporting
confidence: 93%
“…Elderberry contained the highest concentration of TP (17.40 mg.GAE.g -1 FW), by strawberry (14.33 mg GAE.g'1 FW) and bilberry fruits (11.14 mg.GAE g -1 FW). The content of measured TP in our experiment was higher compared to literature data for elderberry (Özgen et al, 2010;Elez Garofulić et al, 2012;Vujanović et al, 2020;Zhou et al, 2020), strawberry (Wang & Lewers, 2007;Peñarrieta et al, 2009;Dyduch-Siemińska et al, 2015) and bilberry (Bunea et al, 2011;Milivojevic et al, 2012;Poiana et al, 2012;Bernal et al, 2014;Celik et al, 2018). Some researchers detected higher amount of TP in elderberry fruits compared to results obtained in our experiment (Tumbas et al, 2010;Colak et al, 2016).…”
Section: Phenolic Compoundscontrasting
confidence: 53%
“…Despite the fact that the presence of cyanidin derivatives in fruit is reported to contribute to a red coloration [ 30 ], the reason for the dark blackberry coloration is an extremely high concentration of cyanidin glycosides. It is the same with elderberries and dark carrots, whose fruits are reflected by a very dark purple, almost black colour, but contain mainly cyanidin derivatives [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast with these findings, some authors reported that cyanidin 3-sambubioside-5-glucoside had higher values (36.4%) than cyanidin 3-glucoside (<20%) [3], while in American elderberry (Sambucus canadensis), cyanidin 3-(trans)-coumaroyl-sambubioside-5-glucoside (65-70%) [49] and cyanidin 3-sambubioside-5-glucoside (~50%) [32] were the most abundant anthocyanins. Nevertheless, it is clear that cyanidin 3-sambubioside, cyanidin 3-glucoside, and cyanidin 3-sambubioside-5-O-glucoside are the most important anthocyanins in elderberries (Sambucus nigra L.).…”
Section: Bioactive Compounds In Elderberriesmentioning
confidence: 78%
“…However, the typical color of these compounds varies with the pH. The elderberries' anthocyanins exhibit red hues at acidic and blue hues at alkaline pH [49]. Particularly, elderberry is used as a food colorant and in pharmaceuticals [26].…”
Section: Bioactive Compounds In Elderberriesmentioning
confidence: 99%